Postural preinspiratory cortical activity, genioglossus activity and fluid shift in awake obstructive sleep apnoea patients. Issue 2 (9th December 2019) - Launois, Claire; Nierat, Marie‐Cécile; Attali, Valérie; Raux, Mathieu; Arnulf, Isabelle; Similowski, Thomas; Redolfi, Stefania
Abstract : New Finding: What is the central question of this study? Transition to supine posture induces an inspiratory load associated with cortical activation in awake healthy subjects. Some obstructive sleep apnoea patients exhibit this cortical activity in the sitting position contributing to the arousal‐dependent compensation of their upper airway abnormalities. Does a transition to the supine posture in awake obstructive sleep apnoea patients increase this cortical activity? What is the main finding and its importance? The transition to supine posture induces a reduction in the cortical activity despite evidence of an increase in genioglossus activity, suggesting that genioglossus activation is not driven by cortical activity. Abstract: The anatomy and mechanical properties of the upper airway (UA) depend on posture. Lying in a supine position causes cephalad fluid shift to the neck, thus narrowing the UA and predisposing the individual to obstructive sleep apnoea (OSA). Increased UA dilator muscle activity during wakefulness prevents the UA collapse but the underlying mechanism has not yet been elucidated. In the sitting position during wakefulness, some OSA patients exhibit preinspiratory cortical activity (preinspiratory potential, PIP) probably related to UA abnormalities. The aim of this study was to investigate changes in the preinspiratory cortical activity and UA dilator muscle in OSA patients during postural challenge. An electroencephalogram was used to detect PIP, and the genioglossus electromyographic activity and ventilation were analysed in 17 awake, male OSA patients while they were sitting, just after lying down, and then in response to leg positive pressure to enhance cephalad fluid shift. The prevalence of PIP decreased from 53% (sitting) to 12% (supine) ( P = 0.002) in association with increased genioglossus activity (tonic from median (25th, 75th centiles) 2.3 (1.8, 2.8)% to 3.6 (1.7, 5.0)% of voluntary deglutition, P = 0.019; phasic from 2.3 (1.9, 2.8)% to 3.7 (2.0, 6.1)%, P = 0.024), and with increased transcutaneous carbon dioxide pressure (from 43.0 (42.4, 44.2) to 44.6 (43.5, 45.2) mmHg). No change was observed during leg‐positive‐pressure application. Moving from the sitting position to the supine position reduces respiratory‐related premotor cortical activity in awake OSA patients. The concomitant increase in genioglossus activity, therefore, is not driven by cortical respiratory activity.